PHYTOCHEMICAL CONTENT AND PHARMACOLOGICAL POTENTIAL OF Melia azedarach L. AS A COMPREHENSIVE STUDY - Aini, Qurratu; Saidi, Nurdin (Jurnal Biologi Sains dan Kependidikan, 2025)
Melia azedarach L., widely known as chinaberry or mindi, is a member of the Meliaceae family that has long been utilized in traditional medicine to treat various ailments such as fever, infections, and diabetes. This study provides a comprehensive review of the phytochemical constituents and pharmacological potential of M. azedarach L. based on a systematic analysis of national and international scientific literature. The findings reveal that the plant contains diverse secondary metabolites including flavonoids (rutin, quercetin), limonoids (salannin, nimbolinin), triterpenoids, phenolic acids, phytosterols, and essential oils. These bioactive compounds contribute to a wide range of biological activities such as antimicrobial, anti-inflammatory, antioxidant, anticancer, antiviral, and antidiabetic effects. Recent studies also highlight its anti-SARS-CoV-2 and immunomodulatory potential through mechanisms involving enzyme inhibition, oxidative stress induction in pathogens, and apoptosis activation in cancer cells. Therefore, Melia azedarach L. represents a promising natural source for the development of phytopharmaceutical products, although further preclinical and clinical studies are necessary to confirm its safety and therapeutic efficacy.